Influence Durian Leaves (Durio zibethinus) Infusion as Natural Anesthesia of Striped Catfish Juvenile (Pangasius sp.) - Dedi Rohendi; Taufik Budhi Pramono; Purnama Sukardi (Universitas Tidar, 2020)
The use of anesthesia in the process of living fish transportation is an effort in keeping the physiology of fish alive and healthy to the destination. Durian leaves are one of the natural ingredients that can be used as fish anesthesia. The purpose of this research is to know the effective concentration of infusum durian leaves as anesthetic seeds of patin fish based on inductive time, sedative time and survival rate. Experimental studies use complete randomized designs, four treatments and threefold. The treatment of infusum concentrations of durian leaves 10%, 20%, 30%, and 40%. The time when fish begins to faint when inserted into the anesthesia solution is recorded as inductive time, whereas the time the fish began to recover back or knowingly recorded as a sedative time. The survival calculation is done on the number of fish surviving post-anesthesia with maintenance for 3 days. The results of this study showed that the effective concentration gained was 10%, with the inductive time (71.67 minutes) distinct from the apparent 20% concentration, but no apparent difference with the concentration of 30% and 40%. Meanwhile, the sedative time (0.25 minutes) differs from the concentration of 40%, but does not differ with concentrations of 20% and 30%. The survival rate of the fish seed Patin at a concentration of 10% showed real distinct results and reached 100%. Infusum concentration of durian leaves by 10% is an effective concentration in the anesthetic process of patin fish seeds.